The bussiness of innovation managing the corporate imagination for maximum results - Bean, Roger (2002)
This is a guide to building innovative, creativity-rich organizations through astute and skillful management. Whatever the end goal, this book provides a systematic process for managing focused, usable innovation - without the micro-managing that can stifle creativity. With examples from McDonald's, Toyota, Palm (Pilot), 3M, Sony, Singapore Airlines and others, this model helps managers and executives: nurture an environment of innovation; support market-focused innovation through effective policies; gather expert feedback to properly evaluate innovations; develop and launch innovations successfully; and project future trends and developments.